Merancang Pembelajaran PAI untuk Penguatan Toleransi Beragama dalam Konteks Multikultural - Mumtahana, Lusia (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
Religious-related social conflicts that occur in several regions in Indonesia have damaged the joints of humanity. This study aims to design PAI Learning Design that focuses on strengthening religious tolerance in SMA Negeri 1 Kedamean, especially in class 11, even the semester with the material ‘Religious Tolerance’. The research used a qualitative method with a case study approach, in which data were obtained from primary and secondary sources through observation, interview, and documentation techniques. Analysis techniques include data reduction, data presentation, and verification, while data validity is tested by triangulation. The results show that religious tolerance education must be given early to foster an open attitude and maintain harmony between religious communities. This learning design is divided into three stages: preparation, implementation, and evaluation, involving students in collaborative projects and hands-on research. This implementation can improve students’ understanding of tolerance as a tool to unify the nation. This research contributes to the development of tolerance-based PAI learning methods that are relevant in the era of multiculturalism and have a significant impact in minimizing intolerant attitudes among students.